Pluralisme Hukum dalam Tradisi Pernikahan Selasa Wage: Perspektif ‘Urf pada Masyarakat Donowangun - Sofi, Nur Malikhatu (Asian Journal of Law and Humanity, 2025)
The implementation of marriage in society is not infrequently influenced by local customs and traditions, so that marriages which are equally based on Islamic law are carried out differently, influenced by the customs of each Muslim community. The Muslim community of Donowangun Village, Talun Sub-district, Pekalongan Regency, preserves many traditions passed down from generation to generation. The tradition of marriage on Tuesday Wage is closely related to the Javanese belief in Javanese calculations (petung) for determining auspicious days or fortune. This paper aims to explain the community's understanding of marriage on Tuesday Wage in Donowangun Village, Talun Sub-district, Pekalongan Regency, and to analyze the 'urf perspective on marriage on Tuesday Wage in Donowangun Village, Talun Sub-district, Pekalongan Regency. This type of research is field research with a qualitative nature, using a normative approach. This research is based on primary and secondary data which includes primary, secondary and tertiary legal materials. The data collection techniques used are interviews, observation, and documentation, with qualitative data analysis methods according to Miles and Huberman and using Islamic law theory of 'urf. The research results show that among the community members who marry on Tuesday Wage in Donowangun Village, some follow the tradition while others do not. Their understanding of following this tradition emerges because it has become a custom inherited from generation to generation and is in accordance with their respective beliefs. Second, from the 'urf perspective, marriage on Tuesday Wage is classified as 'urf shahih (valid custom) because in terms of scope, this tradition does not contradict Islamic law and its principles. This custom is understood as not making the forbidden permissible or nullifying what is obligatory, thus fulfilling religious provisions as legal considerations.